2020
DOI: 10.3390/ma13030553
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Pavement Geomaterials Stabilized with Pond Ash and Brick Kiln Dust Using Advanced Cyclic Triaxial Testing

Abstract: An increase in the generation of industrial waste materials such as pond ash and brick kiln dust represents a serious threat to the earth’s environment. The waste materials have novel characteristics and therefore their physical, chemical, mineralogical, morphological, mechanical, and toxicity characteristics were determined so that these materials can be incorporated as construction materials based on technical and environmental considerations. The purpose of this study is to utilize the wastes in the stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Consequently, the pavement thickness layers were reduced. Moreover, Gupta et al [23] used BKD and pond ash wastes for the stabilization of clay soil to be used as a subgrade layer in the construction of flexible pavements. This research assesses the efficiency of BKD and pond ash in the improvement of the stiffness of clay soil under repetitive loading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the pavement thickness layers were reduced. Moreover, Gupta et al [23] used BKD and pond ash wastes for the stabilization of clay soil to be used as a subgrade layer in the construction of flexible pavements. This research assesses the efficiency of BKD and pond ash in the improvement of the stiffness of clay soil under repetitive loading.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The importance of the study of waste treatment plants concerned with soil pollution and the harmful effects on the environment effects is essentially monitored periodically to ensure the different types of soil characteristics and their strengths are studied thoroughly by qualified and essential team members during the experimentation process (Sharma and Sharma, 2021). The latest software was employed to get adequate results and past results of the soil permeability and its corrosion resistances throughout the concrete materials; flitched materials concerning the different densities ranging from 10 g/m 3 to 100 kg/m 3 are ensured with the help of OSTU technology followed by (Gupta et al, 2020), According to the (Arun et al, 2017), the gradual failures in the soil were found in the order of 5 to 10% compared to last two years; due to the lack of awareness of strengthen characteristics of the lake soil compared to the industry soil; the fragmented release of these minute diffractions defects the entire construction buildings resulting in the high maintenance costs compared to brick concentrates. Hence, it is required to study the properties of the soil, followed by erosion testing, corrosion testing, absorption tests, and diffraction stages.…”
Section: Introductionmentioning
confidence: 99%